2021
DOI: 10.3389/fpsyg.2020.614369
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Image on Psychosocial Outcomes in People With Diabetes and People With an Amputation

Abstract: IntroductionResearch indicates that body image disturbance is associated with poorer psychosocial outcomes for individuals with physical health conditions, with poorest body image reported for individuals with visible bodily changes. Using White’s (2000) theoretical model of body image the present paper aimed to examine the nature of these relationships in two distinct groups: individuals with an amputation and individuals with diabetes. It was hypothesized that body image disturbance would be associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
(21 reference statements)
1
10
0
1
Order By: Relevance
“…Similarly, in youth and young adults of both genders with T1D, body dissatisfaction was described as positively correlated with depressive symptoms (r = 0.71, p < 0.01) (Peterson et al, 2018) and with greater diabetes-specific negative affect (b = 0.05, p < 0.01) (Rancourt et al, 2019). For adults with diabetes (T1 and T2), body image experience, psychological investment in physical appearance, and self-ideal discrepancy predicted psychosocial outcomes such as anxiety, depression, and quality of life (χ 2 = 48.80, p = 0.003; estimate = 0.102) (McDonald et al, 2021). Individuals with T1D with high diabetes distress reported greater shape (test value NR, p < 0.001) and weight (test value NR, p < 0.001) concerns than those with low or moderate distress, regardless of age; among these individuals, those younger than 18 years with high distress perceived a larger current body shape than those with low or moderate distress (test value NR, p < 0.001) (Powers et al, 2017).…”
Section: Psychological Dimensionsmentioning
confidence: 96%
See 4 more Smart Citations
“…Similarly, in youth and young adults of both genders with T1D, body dissatisfaction was described as positively correlated with depressive symptoms (r = 0.71, p < 0.01) (Peterson et al, 2018) and with greater diabetes-specific negative affect (b = 0.05, p < 0.01) (Rancourt et al, 2019). For adults with diabetes (T1 and T2), body image experience, psychological investment in physical appearance, and self-ideal discrepancy predicted psychosocial outcomes such as anxiety, depression, and quality of life (χ 2 = 48.80, p = 0.003; estimate = 0.102) (McDonald et al, 2021). Individuals with T1D with high diabetes distress reported greater shape (test value NR, p < 0.001) and weight (test value NR, p < 0.001) concerns than those with low or moderate distress, regardless of age; among these individuals, those younger than 18 years with high distress perceived a larger current body shape than those with low or moderate distress (test value NR, p < 0.001) (Powers et al, 2017).…”
Section: Psychological Dimensionsmentioning
confidence: 96%
“…Other evidence indicated that adolescents' self-concept in the area of physical appearance mediated both the link between maternal weight and shape concerns and adolescent eating disturbances (pr = 0.42, p = 0.00005) as well as the link between mother-daughter relationships and adolescent eating disturbance status (pr = 0.25, p = 0.003) (Maharaj et al, 2003). For adult individuals with diabetes, body image disturbances mediated the relationship between personal investment in appearance and psychosocial outcomes (estimate = 0.102) and partially mediated the relationship between self-ideal discrepancy and psychosocial outcomes (estimate = 0.185) (χ 2 = 48.80, p = 0.003) (McDonald et al, 2021). For single (not involved in a romantic relationship) adolescents, body image was found to mediate the association between family climate and changes in glycemic control (b = 0.24, p = 0.007) (Hartl et al, 2015).…”
Section: Psychological Dimensionsmentioning
confidence: 98%
See 3 more Smart Citations